Natural Light in Medieval Churches
1 online resource
Keywords: Inside Christian churches, natural light has long been harnessed to underscore theological, symbolic, and ideological statements. In this volume, twenty-four international scholars with various specialties explore how the study of sunlight can reveal essential aspects of the design, decoration, and function of medieval sacred spaces. Themes covered include the interaction between patrons, advisors, architects, and artists, as well as local negotiations among competing traditions that yielded new visual and spatial constructs for which natural light served as a defining and unifying factor. The study of natural light in medieval churches reveals cultural relations, knowledge transfer patterns, processes of translation and adaptation, as well as experiential aspects of sacred spaces in the Middle Ages. Contributors are: Anna Adashinskaya, Jelena Bogdanović, Debanjana Chatterjee, Ljiljana Čavić, Aleksandar Čučaković, Dušan Danilović, Magdalena Dragović, Natalia Figueiras Pimentel, Leslie Forehand, Jacob Gasper, Vera Henkelmann, Gabriel-Dinu Herea, Vladimir Ivanovici, Charles Kerton, Jorge López Quiroga, Anastasija Martinenko, Andrea Mattiello, Rubén G. Mendoza, Dimitris Minasidis, Maria Paschali, Marko Pejić, Iakovos Potamianos, Maria Shevelkina, Alice Isabella Sullivan, Travis Yeager, and Olga Yunak.